Longitudinal Study of Salmonella and Campylobacter Species from Two Laying Duckling Flocks in The Central Region of Thailand - Saengthongpinit, Chalermkiat; Nane-Siri, Dhanapol; Aparachita, Pornpim; Apiwannarat, Prapassorn; Buakhao, Pricha; Bowornnantiwath, Watcharit; Thengchaisri, Naris; Songserm, Thaweesak (The Thai Journal of Veterinary Medicine, 2014)
A longitudinal study was carried out to determine the prevalence of Campylobacter spp. and Salmonella spp. in two laying duckling flocks from the same parent stock. In total, 477 samples: breeding ducks (n=100), 1-day-old female ducklings (n=160), 30-day-old female ducklings (n=178), and environmental (n=39) samples isolated from incubator, soil, water, and feed, were investigated. Results revealed that an overall isolation of Campylobacter spp. was 27.0% (129/477). From the total of 129 positive samples, 56.6% was C. jejuni and 43.4% was C. coli. An overall isolation of Salmonella spp. was 31.0% (148/477). Eight serotypes of Salmonella enterica were identified: S. Amsterdam, S. Chester, S. Dublin, S. Enteritidis, S. Hvittingfoss, S. Mbandaka, S. Montevideo, and S. Thompson. The three most isolated serotypes were S. Montevideo (42.6%), S. Mbandaka (36.5%), and S. Amsterdam (12.8%). The prevalence of Campylobacter spp. and Salmonella spp. in both 1-day-old ducklings and 30-day-old ducklings from both flocks had similar pattern. The prevalence of Salmonella spp. decreased when the 1-day-old ducklings grew to 30-day-old ducklings. However, the prevalence of Campylobacter spp. increased from the age of 1-day-old to 30-day-old. The existence of Campylobacter spp. and Salmonella serotypes in both duck feces and environmental samples was in accordance. In conclusion, our results showed that ducks were normally infected by both Campylobacter spp. and Salmonella spp. possibly originated from environmental contaminations.